2023
DOI: 10.48550/arxiv.2302.06700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DIAmante TESS AutoRegressive Planet Search (DTARPS): I. Analysis of 0.9 Million Light Curves

Abstract: Nearly one million light curves from the TESS Year 1 southern hemisphere extracted from Full Frame Images with the DIAmante pipeline are processed through the AutoRegressive Planet Search statistical procedure. ARIMA models remove trends and lingering autocorrelated noise, the Transit Comb Filter identifies the strongest periodic signal in the light curve, and a Random Forest machine learning classifier is trained and applied to identify the best potential candidates. Classifier training sets include injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Formal statistical time series diagnostics, such as the Shapiro-Wilk and Ljung-Box tests, can determine if the light curves deviate from Gaussian white noise. This is a significant problem: 36% of light curves from TESS Full Frame Images (FFIs) show statistically significant short-memory stochastic variability after spline detrending (Melton et al 2023b, their Figure 5).…”
Section: Difficulties With Detecting Small Transiting Planetsmentioning
confidence: 99%
See 4 more Smart Citations
“…Formal statistical time series diagnostics, such as the Shapiro-Wilk and Ljung-Box tests, can determine if the light curves deviate from Gaussian white noise. This is a significant problem: 36% of light curves from TESS Full Frame Images (FFIs) show statistically significant short-memory stochastic variability after spline detrending (Melton et al 2023b, their Figure 5).…”
Section: Difficulties With Detecting Small Transiting Planetsmentioning
confidence: 99%
“…ARIMA detrending for transiting planet detection was introduced by Caceres et al (2019a) and found to be effective in reducing unwanted light curve variations in most Kepler and TESS light curves (Caceres et al 2019b;Melton et al 2023b). The general utility of ARMA-type modeling for astronomical time-domain studies is discussed by Feigelson et al (2018).…”
Section: Difficulties With Detecting Small Transiting Planetsmentioning
confidence: 99%
See 3 more Smart Citations